Analisis Profil Peserta Webinar Implementasi Kurikulum Merdeka dengan Microsoft Power BI untuk Meningkatkan Akses dan Kualitas Pembelajaran - Kuswayati, Sri; Rusdan, Muchamad; Agustina, Nova (Prosiding SISFOTEK, 2024)
Implementation of Kurikulum Merdeka faces a number of challenges. One of the main challenges is the readiness and competence of educators in understanding and implementing this new curriculum. Implementing webinars has become a popular solution for delivering information and training regarding the Kurikulum Merdeka, but its effectiveness still needs to be further evaluated to ensure that all educators can access and utilize this information well. Analysis of an in-depth understanding of the profile of webinar participants is important to design professional development programs that are more targeted and effective. This research uses Microsoft Power BI and a quantitative descriptive approach which aims to provide an overview of the characteristics of webinar participants based on numerical data collected through participation data. This research population includes all participants from webinar series 1, 2, 3, and 4 regarding the Implementation of the Independent Curriculum. Sampling used a purposive sampling technique, with samples taken from 182 participants who actively took part in the webinar series. The results show that the elementary school level is the type of institution that has the most registrations for the entire webinar series. However, it should be noted that the total number of participants at other levels in each series is relatively small, especially for levels other than elementary school. This may affect the validity of the generalization. This indicates the possibility of other factors influencing the number of registrants at each level. For further research, it is recommended to collect more complete data on participant characteristics, such as geographic location, field of study, and reasons for enrollment.